How to Study the Language Norm Scientifically – Preliminary Issues - Zbróg, Piotr (Respectus Philologicus, 2018)
The article presents an attempt at solving chosen problems related to the preparation to conduct a scientific research of a language norm. Until now, linguists have not attempted at describing the language norm according to its definition. It should be viewed as a social phenomenon. Its research ought to be conducted by the means of mixed methods, including methods inherent to linguistics and social sciences. A proper representative group of contemporary users of the Polish language should be chosen according to the rules applied to regular opinion polls. The questionnaire tools, allowing the creation of situations similar to the natural reaction to correct and incorrect forms, are necessary. In order to evaluate the level of the norm (e.g. model forms, correct forms, acceptable forms), it is necessary to determine the way of interpretation of the obtained results (e.g. more than 85% of positive results qualifies the variant to the model forms, less than 65% – to forms outside the norm). In this way, a reliable image of contemporary language norm would be obtained and a rational basis for the development of the codified norm would be created. There is a high social demand for a reliable source of the way in which Polish should be written and spoken. The constant updating of the normative publications is also necessary, hence the requirement to make them available online. The monitoring of changes of the habit and noting them are equally important.